Glymphatic system dysfunction in young adults hospitalized for an acute psychotic episode: a preliminary report from a pilot study - Barlattani, Tommaso; De Luca, Dalila; Giambartolomei, Sara; Bologna, Antony; Innocenzi, Antonio; Bruno, Federico; Socci, Valentina; Malavolta, Maurizio; Rossi, Alessandro; de Berardis, Domenico; Splendiani, Alessandra; Pacitti, Francesca (Frontiers in Psychiatry, 2025)
The glymphatic system is integral to the elimination of metabolic waste from the central nervous system and has been extensively studied in relation to neurodegenerative and cerebrovascular diseases. Emerging evidence suggests that glymphatic dysfunction may also play a role in psychiatric disorders, including psychosis and schizophrenia. This pilot study investigated glymphatic clearance in young adults hospitalized for an acute psychotic episode using the diffusion tensor imaging (DTI)-derived ALPS (Along Perivascular Spaces) index. Initially, thirteen patients aged 18–30 were recruited; however, only nine completed the DTI protocol due to severe psychiatric symptoms and practical constraints. A non-psychiatric control group comprising twelve individuals was subjected to the same imaging protocol, though precise age matching was not implemented. The study’s findings indicated significant reductions in the ALPS index among patients compared to controls, supporting the hypothesis of impaired glymphatic function during acute psychotic episodes. No significant associations were found between glymphatic clearance and sleep quality, disorganized thinking, or general cognitive functioning. Despite the limitations related to the small sample size, these preliminary results highlight the necessity of further research into the glymphatic system’s involvement in psychosis. Larger-scale studies are required to elucidate the clinical implications and pathophysiological mechanisms linking glymphatic dysfunction to acute psychosis and early psychotic disorders.